Potentially preventable hospitalisations for physical health conditions in community mental health service users: a population-wide linkage study. (10th March 2021) - Sara, G.; Chen, W.; Large, M.; Ramanuj, P.; Curtis, J.; McMillan, F.; Mulder, C.L.; Currow, D.; Burgess, P.
Abstract: Aims: Mental health (MH) service users have increased prevalence of chronic physical conditions such as cardio-respiratory diseases and diabetes. Potentially Preventable Hospitalisations (PPH) for physical health conditions are an indicator of health service access, integration and effectiveness, and are elevated in long term studies of people with MH conditions. We aimed to examine whether PPH rates were elevated in MH service users over a 12-month follow-up period more suitable for routine health indicator reporting. We also examined whether MH service users had increased PPH rates at a younger age, potentially reflecting the younger onset of chronic physical conditions. Methods: A population-wide data linkage in New South Wales (NSW), Australia, population 7.8 million. PPH rates in 178 009 people using community MH services in 2016–2017 were compared to population rates. Primary outcomes were crude and age- and disadvantage-standardised annual PPH episode rate (episodes per 100 000 population), PPH day rate (hospital days per 100 000) and adjusted incidence rate ratios (AIRR). Results: MH service users had higher rates of PPH admission (AIRR 3.6, 95% CI 3.5–3.6) and a larger number of hospital days (AIRR 5.2, 95% CI 5.2–5.3) than other NSW residents due to increased likelihood of admission, more admissions per person and longer length of stay. Increases were greatest for vaccine-preventable conditions (AIRR 4.7, 95% CI 4.5–5.0), and chronic conditions (AIRR 3.7, 95% CI 3.6–3.7). The highest number of admissions and relative risks were for respiratory and metabolic conditions, including chronic obstructive airways disease (AIRR 5.8, 95% CI 5.5–6.0) and diabetic complications (AIRR 5.4, 95% CI 5.1–5.8). One-quarter of excess potentially preventable bed days in MH service users were due to vaccine-related conditions, including vaccine-preventable respiratory illness. Age-related increases in risk occurred earlier in MH service users, particularly for chronic and vaccine-preventable conditions. PPH rates in MH service users aged 20–29 were similar to population rates of people aged 60 and over. These substantial differences were not explained by socio-economic disadvantage. Conclusions: PPHs for physical health conditions are substantially increased in people with MH conditions. Short term (12-month) PPH rates may be a useful lead indicator of increased physical morbidity and less accessible, integrated or effective health care. High hospitalisation rates for vaccine-preventable respiratory infections and hepatitis underline the importance of vaccination in MH service users and suggests potential benefits of prioritising this group for COVID-19 vaccination.